The backside of the postcard: João do Rio wanders by the capital of the Republic - Cury, Maria Zilda Ferreira (Literatura e Sociedade, 1996)
A chronicler of the urban changes undergone by the city of Rio de Janeiro at the beginning of the XX century, João do Rio - flâneur writer that scrutinizes the corroded backside of the social fabric - reveals, whit his allegorical eye, the exiled and dispossessed of the modernization process.